On the Compatibility of Francis Bacon’s Political and Ethical Vision with Islam - Mufti, Malik (Islamic Studies, 2012)
Francis Bacon is a key figure in shaping not just the scientific but also the political features of modernity which are prevailing in the West today, and which are exerting powerful influences elsewhere—including in the Muslim world—as well. Because Bacon’s political writings have received relatively little attention from Muslim thinkers, this article proceeds from one of the few such critiques to analyze some of the more salient features of his political thought as they relate to Islamic concerns. In the course of a review of Bacon’s most relevant treatises, including his Advertisement Touching a Holy War, the article also considers various interpretations—focusing in particular on the Straussian school—of these writings and the apparently contradictory arguments they contain on issues of religion, war and empire. This review gives rise to two primary lines of questioning from an Islamic perspective, one moral and the other political, both suggesting the incompatibility of that perspective with Bacon’s political and ethical standpoints.